An effective transport model of sulfate attack in concrete. (20th August 2019) - Min, Hongguang; Sui, Lili; Xing, Feng; Tian, Hao; Zhou, Yingwu
Highlights: New model captures sulfate ions distributions at different sulfate attack ages. A study of effective diffusivity and its effect on sulfate transport model is presented. An effective transport model of sulfate attack in concrete is presented. Abstract: This paper presents both an experimental and theoretical investigation of the consumed and accumulated rates of sulfate ions in concrete. The authors analyze the effects of sulfate solution concentration and the water-cement ratio on the sulfate ions distribution. Based on the diffusion theory, a sulfate transport model for concrete was established considering the effect of surface sulfate concentration. On this basis, an effective transport model of sulfate attack is presented, which relies on effective diffusivity. This model can be applied to predict the sulfate ions distribution; moreover, its predicted values are in good agreement with the experimental ones.